Rol de los padres de familia y las habilidades interpersonales en la enseñanza semipresencial en niños de la Institución Educativa Inicial N° 60520 Miguel Grau Seminario, Nauta 2022 - Navarro Guerra, Zendy (2023)
The aim of this study was to show the relationship between parental roles and interpersonal skills in co-education for primary school children no. 60520 Miguel Grau Nauta Seminar 2022. The types of research are quantitative. Descriptively, consequently, the population (N) is 48 children from the initial level, the sample size (n) is the census, including 48 children and 48 parents from the initial educational institution number 60520 Miguel Grau Seminario Nauta 2022 Observation was used as a technique, observation manuals as a data collection tool, and the questionnaires were pre-validated by expert evaluation. Conclusions Measure no. 60520 Miguel Seminario Grau Nauta 2022 There was no significant relationship between parental roles and interpersonal skills in blended learning for children.